Does over-the-counter nicotine replacement therapy improve smokers' life expectancy?. Issue 4 (1st December 1998) - Lawrence, William F; Smith, Stevens S; Baker, Timothy B; Fiore, Michael C
Abstract : OBJECTIVE: To determine the public health benefits of making nicotine replacement therapy available without prescription, in terms of number of quitters and life expectancy. DESIGN: A decision-analytic model was developed to compare the policy of over-the-counter (OTC) availability of nicotine replacement therapy with that of prescription (℞) availability for the adult smoking population in the United States. MAIN OUTCOME MEASURES: Long-term (six-month) quit rates, life expectancy, and smoking attributable mortality (SAM) rates. RESULTS: OTC availability of nicotine replacement therapy would result in 91 151 additional successful quitters over a six-month period, and a cumulative total of approximately 1.7 million additional quitters over 25 years. All-cause SAM would decrease by 348 deaths per year and 2940 deaths per year at six months and five years, respectively. Relative to ℞ nicotine replacement therapy availability, OTC availability would result in an average gain in life expectancy across the entire adult smoking population of 0.196 years per smoker. In sensitivity analyses, the benefits of OTC availability were evident across a wide range of changes in baseline parameters. CONCLUSIONS: Compared with ℞ availability of nicotine replacement therapy, OTC availability would result in more successful quitters, fewer smoking-attributable deaths, and increased life expectancy for current smokers.